Perspectives and Challenges of Surrogacy in Iran - H Yousefi; Sh Ghahari (JRI, 2008)
Introduction: Surrogacy is a new approach for treating infertility in couples whose female partner lacks a functional uterus for conceiving or delivering a neonate congenitally or as a result of medical or surgical complications. The procedure has been in practice in Iran for the past few years. Understandably, the procedure has given way to many debates regarding the ethical, psychosocial and legal aspects of the issue. Materials & Methods: We reviewed the literature on surrogacy, as well as related legal issues in other countries. Results: Amazing progresses in infertility treatment have paved the way for people who were desperately seeking a child of their own. This group includes couples whose female partner lacks a functional uterus to conceive and / or deliver a neonate. Surrogacy has made it possible for the couples to achieve their long-lived dream and other women could play the role of surrogate mothers for the couple’s future child, by carrying the fetus in partial or full modes of surrogacy. Separating roles of surrogate mothers and the parenting ones, many controversies regarding ethical, psychological and sociological points of view would rise. Legal problems may rise when a surrogate mother claims the baby. Ethically, the surrogate mothers health, her husbands and childrens consent and the accompanying risks should be taken into account. Probable psychological complications inflicting the mother or her family should not be overlooked too. The point that has raised a lot of opposition and concern is the sociological milieu surrounding the issue; where the procedure may turn to a market to exploit the needy and the poor. Therefore, some countries have adopted strict laws and have formed expert groups to assess and prevent possible problems in practicing surrogacy. Though, most studies depict that surrogacy carries few ethical or psychological problems for the involved parties including the baby. Humanistic aspects and fear of exploiting or abusing the disadvantaged need to be addressed carefully. Conclusion: It seems that ratifying laws regarding surrogacy and forming a committee to evaluate all aspects of surrogacy may prevent the probable aforementioned problems.
Keywords: Infertility, Surrogate uterus, Ethical issues, Legal issues, Psychological, Social aspects, Consultation